Four urban health paradigms: The search for coherence. (September 2022) - Kim, Jinhee; de Leeuw, Evelyne; Harris-Roxas, Ben; Sainsbury, Peter
Abstract: Scholars, practitioners and policymakers view urban health based on their foundational ontologies, or paradigms, which provide a framework of norms that specifies the policy goals or research questions, the preferred policy instruments or research methodologies, and defines the nature of the urban health issue. This paper identifies four paradigms in current research and practice that address the links between the urban built environment and human health: the ' medical-industrial city ', 'urban health science', ' healthy built environment ' and ' health social movement ' paradigms. We argue that scholars, practitioners and policymakers must recognise their diverse and sometimes contradictory views in order to create an opportunity for coherence in understanding knowledge generated from different paradigms. Highlights: A paradigmatic lens is applied to identify the diverse approaches applied to urban health. Urban health paradigms differ in how the priority issues and the methodologies to address those issues are conceptualised. Understanding the multiple views creates an opportunity for coherence among the approaches.